Distribution of diabetes, hypertension and non-communicable disease risk factors among adults in rural Bangladesh: a cross-sectional survey. Issue 6 (12th November 2018) - Fottrell, Edward; Ahmed, Naveed; Shaha, Sanjit Kumer; Jennings, Hannah; Kuddus, Abdul; Morrison, Joanna; Akter, Kohenour; Nahar, Badrun; Nahar, Tasmin; Haghparast-Bidgoli, Hassan; Khan, A K Azad; Costello, Anthony; et al.
Abstract : Background: Non-communicable diseases (NCDs) are increasing in low-income settings. We conducted a survey of risk factors, blood pressure and blood glucose in rural Bangladesh and assessed variations by age, sex and wealth. Methods: We surveyed a random sample of 12 280 adults aged > 30 years in 96 villages in rural Bangladesh. Fieldworkers measured blood glucose and conducted an glucose tolerance test with a repeat blood test 120 min post glucose ingestion. Blood pressure, anthropometric, socioeconomic, lifestyle and behavioural risk factors data were also collected. Data were analysed to describe the prevalence of diabetes, intermediate hyperglycaemia, hypertension and NCD risk factors by age, sex and wealth. Results: Women had higher levels of overweight or obesity and lower levels of physical activity and fruit and vegetable consumption than men; 63% of men used tobacco compared with 41.3% of women. Overweight or obesity and abdominal obesity (waist to hip ratio) increased with socioeconomic status (least poor vs most poor: OR (95% CI) 3.21 (2.51 to 4.11) for men and 2.83 (2.28 to 3.52) for women). Tobacco use, passive smoke exposure and salt consumption fell with increasing socioeconomic status in both sexes. Clustering of risk factors showed more than 70% of men and women reported at least three risk factors. Women in the least poor group were 33% more likely to have three or more risk factors compared with women in the most poor group (1.33 (95% CI 1.17 to 1.58)). The combined prevalence of impaired fasting glucose, impaired glucose tolerance and diabetes was 26.1% among men and 34.9% among women, and increased with age. The prevalence of prehypertension and hypertension was 30.7% and 15.9% among men and 27.2% and 22.5% among women, with similar rising prevalence with age. Conclusion: NCD risk factors, hyperglycaemia and raised blood pressure are an immediate health threat in rural Bangladesh. Initiatives to improve detection, treatment and prevention strategies are needed.